TAX AVOIDANCE: BERKAIT DENGAN DERIVATIF KEUANGAN SERTA FIXED ASSET INTENSITY - Airlin Permata Sari; Andrik Gastri Widjatmiko; Yety Anggraini; Wahyu Wismawati (ITB AAS Indonesia Surakarta, 2025)
This research begins with the concern that the realization of total tax revenue does not meet expectations. This study examines 37 banking companies, comprising a total of 292 firm-year samples, using panel data regression analysis methods. Based on the findings, it can be concluded that the financial derivative variable has a positive influence on tax avoidance. Additionally, the fixed asset intensity variable also has a negative impact on tax avoidance. Ultimately, this research is expected to provide contributions to companies, future researchers, and stakeholders regarding tax avoidance.